The enforcement of capital punishment in corruption crimes within Indonesia’s legal system from human rights perspective - Fadillah, Ahmad Wasli (Trigin Publisher, 2025)
This study examines the enforcement of capital punishment in corruption crimes within Indonesia’s legal system through the lens of human rights theory and constitutional law. Using a normative juridical approach, the research explores the philosophical, legal, and moral foundations of the death penalty as prescribed in Law No. 31 of 1999 in conjunction with Law No. 20 of 2001, juxtaposed against Indonesia’s human rights obligations under the 1945 Constitution and international covenants. The discussion integrates natural rights theory, utilitarian human rights theory, and progressive human rights theory to analyze the ethical legitimacy and legal coherence of capital punishment for corruption. Findings reveal a fundamental contradiction between Indonesia’s retention of the death penalty and its constitutional guarantee of the right to life. While corruption constitutes an extraordinary crime that threatens national stability, capital punishment fails to meet international standards of necessity and proportionality. The paper argues that true deterrence and justice lie in systemic legal reform, transparency, and moral governance rather than retributive punishment. Ultimately, this study advocates for the gradual abolition of capital punishment in favor of a human rights–based penal policy consistent with Indonesia’s democratic and humanitarian values.